Limb-belt resisted sprint training improves physical fitness and ball-throw velocity in pubertal handball players - Emna Makni; Firas Zghal; Raouf Hammami; Mohamed Abdelkader; Raghad Tarwneh; Mohamed Elloumi (Biology of Sport)
The study assessed the effect of six weeks of biweekly upper and lower limbs’ weighted-belt resisted sprint training (BRST) and weighted-vest resisted sprint training (VRST), or normal sprint training (NST) on muscle strength, speed, change of direction and handball-throwing velocity in young handball players. Twenty-seven pubertal male handball players aged 14.4 years were randomly assigned into BRST ( n = 9), VRST ( n = 8), and NST ( n = 8) groups. Sprint ability (10-m and 30-m), squat jump (SJ), countermovement jump (CMJ), free-arm countermovement jump (CMJFA), standing long jump (SLJ), Five-jump test (FJT), change of direction and handball-throw velocity were assessed before and after a 6-week training in season program. Within-group interactions showed that BRST improved all tests’ performances (moderate-to-large). VRST improved sprint, SLJ, FJT and handball-throw velocity performances (small-to-large). NST improved only the change of direction performances (moderate). Between-groups comparison revealed that BRST improved all testing performances, except change of direction, compared with NST (large) and improved 30-m sprint, CMJFA, FJT and handball-throw velocity performance compared with VRST (moderate-to-large). In addition, VRST improved 30-m sprint, SJ and handball-throw velocity performances compared with NST (moderate-to-large). Throwing performance changes correlated with changes in sprint time and horizontal and vertical jump abilities ( r = 0.40 to r = 0.69; p < 0.01). We conclude that while both resisted sprint training improved players’ sprint, jumping and handball-throw performances, substantial improvements were recorded with the BRST compared to VRST and NST. Thus, BRST could be recommended to male U15 handball players as a valuable training method for developing physical fitness and skill performances.